Framework for risk communication and community engagement to improve vaccine uptake for COVID-19 and other vaccine-preventable diseases in low- and middle-income countries (LMIC) - Gonah, Laston; Kobie, Aminata Grace (Ubiquity Press, 2022)
A framework for guiding risk communication and community engagement (RCCE) during COVID-19 vaccination roll-out is worthwhile in order to guide interventions aimed at improving vaccine uptake. This requires setting up standardised early-warning indicators to predict or detect low uptake; coordination of response activities by all partners, real-time information exchange, innovativeness in designing strategies to deal with arising and anticipated challenges; flexibility to adapt quickly to changing demands and evolving circumstances; and documentation of progress and lessons learnt.